Penerapan Relaksasi Benson terhadap Kecemasan pada Ibu Hamil Dengan Preeklamsia - Aisyah; Irwan Agustian; Fitri Handayani (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Preeclampsia is a pregnancy complication that causes anxiety in pregnant women and potentially increases risks for both mother and fetus. Anxiety in pregnant women can be managed using non-pharmacological therapies, such as Benson's relaxation. This study aims to determine the outcomes of implementing Benson's Relaxation on Anxiety targeting Pregnant Women with Preeclampsia in the Sukarahayu Community Health Center (Puskesmas) Work Area. The research method used was descriptive with a case study approach involving three anxious pregnant women with preeclampsia. Anxiety levels were measured using the Perinatal Anxiety Screening Scale (PASS) questionnaire. The Benson relaxation intervention was administered for 3 days, twice a day, with a duration of 15 minutes per session. The results showed a decrease in anxiety levels in all three patients. In Patient 1, there was a reduction from severe anxiety with an anxiety score of 65 to mild anxiety with a score of 36; Patient 2 decreased from mild anxiety with a score of 33 to no anxiety with a score of 20; and Patient 3 decreased from severe anxiety with a score of 45 to mild anxiety with a score of 29. Benson's Relaxation successfully reduces anxiety in pregnant women with preeclampsia. This therapy can be utilized as an easy, safe, and independent non-pharmacological intervention to help control anxiety during pregnancy. Nurses are expected to provide education and guidance so that this technique can be performed independently by patients, alongside a longer intervention period to achieve more optimal results.